Diversity of hepatitis B and C viruses in Chile - Di Lello, Federico Alejandro (2009)
Although there is a low prevalence rate (around 1% of the population) of infection with hepatitis B virus (HBV) and hepatitis C virus (HCV) in Chile, little is known about the diversity and molecular characteristics of the circulating viruses. In the present study, 40 HBV and 57 HCV samples from Santiago City, Chile, were examined. The phylogenetic analysis of HBV samples showed the autochthonous genotype F as the most represented genotype in the study (67.5%), while genotypes A, B, C, and D were less frequent (7.5%, 5%, 7.5%, and 12.5%, respectively). The frequency of circulation of HBV genotypes observed is in accordance with the genetic background of the Chilean population. Most of the HCV samples tested belonged to subtype 1b (82%). The coalescent analysis conducted for both the NS5A and NS5B regions of the HCV strains showed similar population growth rates, with a most recent common ancestor estimated to date between 1893 and 1901. This result may indicate that genotype 1b strains circulating in Chile have epidemiological features similar to those described for HCV genotype 1b in Brazil and the United States. However, the most recent common ancestor for Chile is older than that reported recently for genotype 1b in Argentina.